Comprehensive Injury Prevention Strategies in Gymnastics: A Systematic Review of Biomechanical and Training-Related Risk Factors - Lubis, Hafiz Yazid; Corwin , Patsy; Kharatzadeh, Masoud; Kessler , Phoebe (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2025)
The purpose of the study. To comprehensively analyze gymnastics injury prevention research, evaluate existing safety protocols, and identify best practices for reducing injury risks in middle school and competitive gymnastics programs through a systematic review of recent literature. Materials and methods. A systematic literature review was conducted following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) methodology. The study examined peer-reviewed articles published between 2012 and 2024, focusing on human participants and injury prevention in gymnastics. A comprehensive electronic search was performed across multiple academic databases, utilizing search terms including